Ecological risk assessment of oceanic tuna fisheries on secondary species in the sea of Vietnam - Ha, Vu Viet; Thanh, Tran Van; Son, Hoang Ngoc; Thuy, Nguyen Thi Dieu (Vietnam Journal of Marine Science and Technology, 2019)
Ecological risk assessments of the oceanic tuna fisheries on the secondary species in the Sea of Vietnam were conducted following the productivity and susceptibility analysis (PSA) method suggested by Marine Stewardship Council. The secondary species were identified through compilation and analysis of data collected in 67 observer trips conducted on board of commercial tuna fisheries by Research Institute for Marine Fisheries (RIMF) and WWF-Vietnam during the period 2000-2016. The consequence analysis pointed out that there were 12 secondary species of tuna fisheries which were taken into PSA analysis. The results indicated that most of species were at medium and low risk level. Species considered at medium risk are Pelagic thresher (Alopias pelagicus), Blue shark (Prionace glauca), Scalloped hammerhead (Sphyrna lewini), Wahoo (Acanthocybium solandri), Escolar (Lepidocybium flavobrunneum), Indo-Pacific sailfish (Istiophorus platypterus) and at low risk are Longtail tuna (Thunnus tonggol), Swordfish (Xiphias gladius), Snake mackerel (Gempylus serpens), Black marlin (Makaira indica), Indo-Pacific blue marlin (M. mazara) and Common dolphinfish (Coryphaena hippurus). Yellowfin Tuna (Thunnus albacares) and Bigeye Tuna (T. obesus) are target species and both at ecologically low risk level. The results also showed that tuna handline fishery has less impacts on group of secondary species compared to longline fishery.